Bibliometric Analysis of Audit Quality Using VOSviewer: A Study of Publications from 2020 to 2023 - Bria, Valerianus (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
This study aims to analyze the development of audit quality research from 2020 to 2023 using bibliometric analysis and VOSviewer. The research focuses on identifying publication trends, country contributions, and institutional productivity and citations. A quantitative descriptive method was applied, using Scopus data retrieved via Publish or Perish with the keyword “audit quality.” VOSviewer was used to visualize keyword clusters and research gaps. The results show that 2023 had the highest number of publications (288 articles), with the United States leading in total documents (315). Indonesia published 64 articles during the same period, but no institution exceeded three publications. Keyword mapping revealed six clusters, with underexplored topics such as audit report lag and non-audit service. These findings suggest future research opportunities in less-studied areas of audit quality, especially in emerging economies.